Diagnostic Value of Repeated Stool Sampling in Intestinal Helminth Infections Detection in Makenene, Cameroon - Martin Gael Oyono; Astride Adriane Magnanock; Jean Thierry Ebogo-Belobo; Siporah Osvalde Abe Ngono; Brunelle Tchakounte Betbeu; Leonel Javeres Mbah Ntepe; Serge Eteme Enama (Journal of Life Science and Public Health, 2026)
Intestinal helminthiases remain among the most prevalent neglected tropical diseases worldwide, disproportionately affecting school-aged children in low- and middle-income countries. Despite the WHO 2021–2030 roadmap targeting the elimination of schistosomiasis and soil-transmitted helminths as public health problems, limitations in diagnostic sensitivity continue to hinder accurate prevalence estimates and effective monitoring. This study assessed the prevalence of intestinal helminth infections among school-aged children using repeated stool sampling in the Makenene subdivision. In this cross-sectional survey, two stool samples were collected from 152 eligible children, obtained 48 hours apart, each examined using duplicate Kato-Katz thick smears, yielding four slides per participant for parasitological analysis. In the first sampling period, Schistosoma mansoni prevalence was 9.21%; in the second period, it rose to 10.52%, reflecting the added sensitivity of repeated sampling. The overall prevalence across both sampling periods was 11.18%. Agreement between the first and second stool samples was almost perfect (κ = 0.873; 95% CI: 0.760–0.986, p < 0.0001), with the second stool sample contributing an absolute diagnostic gain of 1.3 percentage points. Additional helminths identified included Ascaris lumbricoides (4.60%), Trichuris trichiura (2.63%), and hookworm species (0.65%). These findings confirm ongoing transmission of intestinal helminths in Makenene, with S. mansoni as the predominant parasite, and underscore the importance of repeated stool sampling for accurate prevalence estimated and monitoring of control programmes in endemic settings.